Costs of Stroke Treatment Under National Health Insurance at Dr. Mohammad Hoesin General Hospital - Pinto Desti Ramadhoni; Achmad Junaidi; Lenny Octavinawaty; Apriyono Apriyono; Ardy Oktaviandi (Journal of Neurointervention and Stroke, 2025)
Highlight: Discrepancy in costs hospitalization Prevalence and risk factors ABSTRACT Introduction: Indonesia’s National Health Insurance/Jaminan Kesehatan Nasional (JKN) consider stroke a catastrophic disease due to its high treatment costs and healthcare system burden. Stroke patients need extended hospitalization, advanced procedures, and long-term rehabilitation, making it financially and socially burdensome. Endovascular procedures like mechanical thrombectomy and coiling improve clinical outcomes but are expensive. Objective: To outline the characteristics and hospitalization costs of stroke patients—both ischemic and hemorrhagic—covered by JKN at Dr. Mohammad Hoesin General Hospital, focusing on cost differences among conservative therapy, thrombolysis, mechanical thrombectomy, and coiling.  Method: A descriptive study with retrospective data collection was performed at a Type A hospital in South Sumatra, using patient records from January to April 2024. Result: Ischemic stroke was the most common type, with most patients aged 46-65 and male. Most patients stayed less than ten days on second-class wards. Conservative therapy was the most frequently used treatment. Hypertension and kidney disorders were the biggest risk factors and comorbidities. Hospital charges for mechanical thrombectomy and coiling exceeded INA-CBG (Indonesian Case Based Groups) reimbursement rates, highlighting a substantial gap between actual hospital costs and insurance coverage. For both stroke types, medication costs dominated total expenses. Conclusion: The significant gap actual hospital costs and INA-CBG reimbursement  rates for stroke treatments, especially for mechanical thrombectomy and coiling, may affect hospital policies on these interventions. To ensure long-term stroke management, revisions to reimbursement schemes should take into account the high costs associated with endovascular therapy.